The effect of task complexity in dialogic oral production by Indonesian EFL learners - Mahpul; Oliver, Rhonda (2018)
In EFL settings opportunities to practice meaningful use of English are often limited and this is the case in Indonesia \ the context of the current study - where teachers often favor traditional approaches to language learning. To address this, task based approaches to language teaching are being promoted internationally as a way to provide opportunities for language learning. This is because the use of tasks in an EFL classroom context provides learners with learning activities that reflect real life situations and language is used by learners in ways that are facilitative of their second language acquisition. However, many English language teachers are unsure of which tasks and tasks conditions are best for their learners. Informed by the Cognition Hypothesis (Robinson, 2001a, 2001b, 2003, 2005, 2007), this study investigates the effect of manipulating different task conditions, namely planning time and the number of elements on L2 learner performance of dialogic tasks, as measured by complexity, accuracy and fluency (CAF). 52 Indonesian learners of English performed four tasks, each involving different task conditions. The results only partially support the predictions of the Cognition Hypothesis. However, they do provide directions for teachers about how to use tasks to potentially promote learners' language performance in terms of complexity, accuracy and fluency.